SINTESIS PALMITOIL DAN LAUROIL ETANOLAMIDA MENGGUNAKAN PELARUT CAMPURAN : PENGARUH TEMPERATUR DAN WAKTU REAKSI - Muhammad Ashari; Nur Annisa; Zuhrina Masyithah (Jurnal Teknik Kimia USU, 2017)
Surfactant is a molecule which has hydrophilic group and a lipophilic group which can unify a mixture consisting of water and oil. Alkanolamide is a type of widely used nonionic surfactant for various purposes. In this study, we observed the effect of temperature and reaction time on the synthesis of palmitoyl ethanolamide surfactant from palmitic acid and lauroyl ethanolamide from lauric acid with zirconium (IV) chloride as catalyst in mixed solvent. This research was conducted using amidation reaction at temperature variation of 55oC, 65oC, 75oC, 85oC and 95oC, reaction time variation of 1 hour, 2 hours, 3 hours, 4 hours, and 5 hours, mole substrate ratio at 1:10, solvent ratio at 2: 1 (v / b), catalyst concentration 5% (w/w), and stirring rate at 250 rpm. Then the product was analyzed by FT-IR spectrophotometry. Based on this research, the optimum condition to synthesis palmitoyl ethanolamide surfactant was obtained at 55 oC and temperature 65 oC to synthesis lauroyl ethanolamide surfactant at reaction time of 3 hours for both of them.